2018
DOI: 10.1002/srin.201800354
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Gasification Reaction Behavior and Kinetic Analysis of Iron Coke Hot Briquette under Isothermal Conditions

Abstract: Gasification reaction behavior of iron coke as well as kinetic parameters is extremely important for its quality evaluation and practical application in an actual blast furnace. However, there are few researches on the gasification behavior of iron coke, especially for iron coke hot briquette (ICHB) prepared by hot briquetting process. In this paper, the gasification reaction behavior of ICHB is experimentally investigated under isothermal conditions. Meanwhile, the kinetic analysis for the gasification proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…The addition of Fe2O3 reduced CSR from 61.94% to 42.78%. These results are consistent with the previous studies [8][9][10][11][12][13][14][15][16][17].…”
Section: Strength Degradation Of Iron Coke Prepared By Mixed Coal And...supporting
confidence: 94%
See 1 more Smart Citation
“…The addition of Fe2O3 reduced CSR from 61.94% to 42.78%. These results are consistent with the previous studies [8][9][10][11][12][13][14][15][16][17].…”
Section: Strength Degradation Of Iron Coke Prepared By Mixed Coal And...supporting
confidence: 94%
“…Many studies show that [8][9][10][11][12][13][14][15][16][17] iron-containing substances are harmful to the strength of iron coke while catalyzing its reactivity, especially to the index of coke strength after reaction (CSR). As a result, the role of iron coke in the blast furnace is weakened, which is not conducive to its application in the blast furnace.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous research, showing that the reduction of iron oxide, oxidization of metal iron, and generation reaction of fayalite simultaneously occur during the gasification process of iron coke. [ 30 ] The mechanism of the mass loss reaction can be described by the following reaction.CO2 + C = 2COFeO + CO = Fe + CO22FeO + C = 2Fe + CO2…”
Section: Resultsmentioning
confidence: 99%
“…The initial compressive strength of iron coke with 40% iron ore content reaches >3800 N, while it decreases to <2000 N when roasted at 1150 °C for 30 min under a CO 2 atmosphere. The high-temperature compressive strength of iron coke with 40% iron ore content decreases around 40% when the CO 2 gasification roasting period increases from 30 to 90 min at 1100 °C.…”
mentioning
confidence: 99%
“…The powder mixture is mixed and agglomerated by either a cold-bonded or hot-bonded method . Thus far, quantitative studies have been carried out on the optimization of CCB physiochemical properties, in terms of selection of raw materials, component blending ratio, and briquetting–carbonization conditions. , It is shown that CCB can be reduced faster than ordinary iron ore because of the close contact among particles, where mutual promotion of chemical reactions (carbon gasification and iron oxide reduction) can occur. Also, the strengths before and after the chemical reaction are quite different when, for example, adopting different component ratios. , On the other hand, apart from CCB properties, it is necessary to systematically investigate CCB physiochemical behaviors, especially those under actual BF conditions. CCB reaction behaviors have been studied under many conditions using various methods.…”
Section: Introductionmentioning
confidence: 99%